2019
DOI: 10.3389/feduc.2019.00085
|View full text |Cite
|
Sign up to set email alerts
|

Does Teacher Collaboration Improve Student Achievement? Analysis of the German PISA 2012 Sample

Abstract: During the past decades, teacher collaboration has received increasing attention from both the research and the practice fields. However, little has been said about its relationship with student achievement. In the present study, using data from the representative PISA 2012 German sample, we investigate the effects that the three forms of teacher collaboration proposed by PISA namely instruction-project-and organization related have on student achievement. We conducted exploratory and confirmatory factor analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 49 publications
(49 reference statements)
4
10
0
1
Order By: Relevance
“…This means that teacher collaboration appears to be effective in improving students' achievement. This finding resounds that of Mora-Ruano et al (2019) that teachers' collaboration can be effective in improving students' achievement if their learning needs are discussed during the collaborative activities. It also resonates with the finding of Ronfeldt et al (2015) that high-quality collaboration among teachers is associated with an increase in students' achievement in mathematics and reading.…”
Section: Discussionsupporting
confidence: 52%
“…This means that teacher collaboration appears to be effective in improving students' achievement. This finding resounds that of Mora-Ruano et al (2019) that teachers' collaboration can be effective in improving students' achievement if their learning needs are discussed during the collaborative activities. It also resonates with the finding of Ronfeldt et al (2015) that high-quality collaboration among teachers is associated with an increase in students' achievement in mathematics and reading.…”
Section: Discussionsupporting
confidence: 52%
“…It must be noticed that not all forms of collaboration are necessarily positively related on every aspect of the school. For instance, Mora-Ruano et al (2019) showed a negative relationship between the exchange form of collaboration and student achievement. Therefore, enhancing such types of collaboration may fail to increase student achievement.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The new generation of students demands new teaching practices (Vega-Burgos et al, 2011;Herodotou et al, 2019). Our results point out the importance of professor collaboration (Mora-Ruano et al, 2019), implying the need for educators, at least in Latin America, to make certain that the activities in the classrooms increase student emotional intelligence or orientation to happiness. An example would be the Mindfulness and Emotional Intelligence Program (PINEP), which is a virtual program that has been proven to enhance students' positive traits (Salcido-Cibrián et al, 2019).…”
Section: Discussionmentioning
confidence: 63%